TOURISM DEVELOPMENT MODEL THROUGH A BIOREGION APPROACH CASE STUDY OF MBAH DJOE RESORT TOURISM (International Conference of Graduate School on Sustainability (ICGSS), 2018)
"Mbah Djoe Resort" is a tourist attraction built by individuals in which there are various facilities supporting tourism activities, located in Kelurahan Sarangan, Kecamatan Plaosan - Magetan. This place utilizes natural conditions and fertile plantation land as the main object. The arrangement of tourism objects and their physical development becomes a new node in the regional or cross-regional scope and becomes a new space in activities. Regional growth in terms of spatial and geographical conditions, development activities carried out indiscriminately and uncontrollably, have ecologically potential that can damage the availability of natural resources. Patterns and systems of natural resource management that are based on sustainability need to be implemented, because natural resources are the most important thing from the carrying capacity of the environment, so the effects of damage can stop natural resource-based businesses, harm tourism, social conflicts, environmental pollution, land landslides and result in a decrease in the welfare of the community with the loss of employment. The use and management of the preservation of natural resources and the environment can improve equity and social status, so that it needs comprehensive and integrated planning through a bioregion approach, the aim is that the developed tourism environment has certain characteristics or characteristics with boundaries determined by the natural order and its main component is human culture so that it can synergize and be integrated with other regions in a harmonious, borderless, sustainable and directed manner, because the concept of bioregion is a balance between humans and nature. The method used in this study is Descriptive Qualitative with qualitative analysis techniques. From discussion, management of the area and natural resources using the bioregion approach provides benefits in terms of ecology, economics and socio-culture, because in these uses are related to biological components as well as ecosystems and humans which is an absolute requirement to ensure the sustainability of natural processes that occur in the region.